PERANAN IKATAN MAHASISWA MUHAMMADIYAH (IMM) DALAM MEMBENTUK PERILAKU BERAGAMA MAHASISWA DI PERGURUAN TINGGI MUHAMMADIYAH - Imam Pribadi (Voice of Midwifery, 2016)
This thesis is aimed to describe the role of Ikatan Mahasiswa Muhammadiyah (IMM) in changing the religious behavior of the students of Perguruan Tinggi Muhammadiyah Palopo, in which its problem is described in three sub-problems, as follows: to find out the role of Darul Arqam Dasar, Darul Arqam Madya, and Islamic studies toward the change of the students' religious behavior at Perguruan Tinggi Muhammadiyah Palopo, to find out the supporting factors and the obstacles of the change of the students' religious behavior at Perguruan Tinggi Muhammadiyah Palopo, to find out the solution to cope with the obstacles of the change of the students' religious behavior at Perguruan Tinggi Muhammadiyah Palopo.This research is a qualitative research with primary data source taken from Perguruan Tinggi Muhammadiyah Palopo through the interviews with the main informants, and the secondary data are the literatures and the related questionnaires. The data collecting instrument is the researcher as human instrument to determine the research focus, to collect the data, to assess the data quality, to interpret the data, and to make conclusion. The interview guide, observation, and documents are the complements.The findings and the data analysis show that there is a significant influence of the formal trainings and Islamic studies of Ikatan Mahasiswa Muhammadiyah (IMM) " toward the change of the studentligious behavior at Perguruan Tinggi Muhammadiyah Palopo. This is because of the training process and studies are conducted to encourage the students to improve their faith, worship, and morality. The outputs the training are expected to have tauhid-based aqidah, consistency in performing worship, high morality, and fighting spirit or spirit of movement. Key words : Ikatan Mahasiswa Muhammadiyah, Change, behavior, religious